2007
DOI: 10.1016/j.bpc.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein-surfactant interactions: A calorimetric and spectroscopic investigation of the phytase-SDS system

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A C C E P T E D M A N U S C R I P T ACCEPTED MANU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…The majority of the works published in this field deal with the nature of the interaction of these proteins with anionic surfactants, whereas the number of publications addressing the effect of cationic and non-ionic surfactants on various proteins is much lower [24]. The most extensively studied anionic surfactants are sodium dodecyl sulfate (SDS) [25][26][27][28][29][30][31][32][33] and sodium alkyl sulfates with various carbon chain lengths. Research by Lu et al revealed that the interaction between surfactant and protein is only slightly affected by the nature of the polar part of the surfactant and much more by the length of the apolar carbon chain [34].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the works published in this field deal with the nature of the interaction of these proteins with anionic surfactants, whereas the number of publications addressing the effect of cationic and non-ionic surfactants on various proteins is much lower [24]. The most extensively studied anionic surfactants are sodium dodecyl sulfate (SDS) [25][26][27][28][29][30][31][32][33] and sodium alkyl sulfates with various carbon chain lengths. Research by Lu et al revealed that the interaction between surfactant and protein is only slightly affected by the nature of the polar part of the surfactant and much more by the length of the apolar carbon chain [34].…”
Section: Introductionmentioning
confidence: 99%
“…6). When SDS denaturation occurs at concentrations below the critical micelle concentration, protein oligomer dissociation rather than subunit denaturation is typically observed [26, 29]. The relatively small numbers of SDS molecules that bind to MfpA as well as the changes in the spectral measures are consistent with this view.…”
Section: Resultsmentioning
confidence: 91%
“…3B & 5A). The two negative peaks at ~ 206 nm and 222 nm are characteristic of proteins in SDS [26, 27], that typical of α/β proteins [21] and completely different from that of the native MfpA [4, 6]. The fluorescence emission λ max red shifts to ~ 342 nm indicating increased exposure of the Trp residues, again recapitulating urea refolded MfpA (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The low binding number may however be due to a combination of several disulfide bonds and the heavy glycosylation of the linker. Glycosylation has previously been shown to decrease the amount of SDS which binds to enzymes (Bagger et al, 2007). In contrast to SDS, CZ titrations with RL overlapped with RL titrations into buffer ( Figure 9D).…”
Section: Titration Of Sds and Rl Into Czmentioning
confidence: 80%
“…ITC provides valuable information about the thermodynamics and stoichiometry of binding as shown in several studies (Nielsen et al, 2005(Nielsen et al, , 2007Bagger et al, 2007;Andersen et al, 2008Otzen et al, 2009). Different protein concentrations of the three enzymes were therefore subjected to titrations with SDS and RL and the recorded heat flow was accordingly analyzed.…”
Section: Itc Reveals Major Differences In the Binding Stoichiometry Omentioning
confidence: 99%